Experimental analysis of Energy and Environment redeemable in solar Nano-basin still to improve Sullage Water Natural Treatment of Fuzzy Application. (2019) - Suresh, C.; Shanmugan, S.; Bharath, M.V.; Naveen, B.; Chithambaram, V.
Abstract: This paper studies the thermal performance of a single basin solar still whose five sides are exposed to ambient and supplies are also providing to connect the glasses to augment the intensity of occasion solar radiation on the range. The experimental analysis of thermal techniques (Solar Nano-basin still) in sullage water treatment fuzzy logic techniques are used to produce clean water from energy of sun. Intension of the sullage water into clean water has been performed of clear sunny day on summer and winter seasons at Vel Tech Multi Tech Dr.Rangarajan Dr. Sakunthala Engineering College. It is an innovative to reduce the fluid waste is called water quality conversion and one of the days in system has been given the 24 hr cycle, the total drip production is found to be 7.624 kg/m 2 day and without drip 5.254 kg/m 2 day and Overall efficiency is 45%. As compared to mixed nano-black paint, selective surface coating results in significantly higher oven temperatures (up to 66 o C).